Odpowiedź :
c=26-3b
3a=21-b
a=21-b/3
podstawiamy do trzeciego równania
3(26-3b)+21-b/3=29 pomnożymy obie strony przez 3
9(26-3b)+21-b=87
234-27b+21-b=87
-28b=-168
b=6
c=26-18
c=8
a=5
3a=21-b
a=21-b/3
podstawiamy do trzeciego równania
3(26-3b)+21-b/3=29 pomnożymy obie strony przez 3
9(26-3b)+21-b=87
234-27b+21-b=87
-28b=-168
b=6
c=26-18
c=8
a=5
3a+b=21
3b+c=26
3c+a=29 dodaj wszystkie
4(a+b+c)=76
a+b+c=19==> a=19-b-c
57-3b-3c+b=21===>2b+3c=36
3b+c=26==>9b+3c=78==>3c=78-9b podstawiam do powyzszego
2b+78-9b=36
7b=42
b=6
3a+6=21 ==> a=5 czyli c=8
3b+c=26
3c+a=29 dodaj wszystkie
4(a+b+c)=76
a+b+c=19==> a=19-b-c
57-3b-3c+b=21===>2b+3c=36
3b+c=26==>9b+3c=78==>3c=78-9b podstawiam do powyzszego
2b+78-9b=36
7b=42
b=6
3a+6=21 ==> a=5 czyli c=8